2020
DOI: 10.1007/s00436-020-06745-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evaluation of invasive Lactobacillus plantarum co-expressing EtMIC2 and chicken interleukin-18 against Eimeria tenella

Abstract: Chicken coccidiosis is a protozoan parasitic disease that leads to considerable economic losses in the poultry industry. In this study, we used invasive Lactobacillus plantarum ( L.P ) expressing the FnBPA protein as a novel bacterial carrier for DNA delivery into epithelial cells to develop a live oral DNA vaccine. A fusion DNA vaccine co-expressing EtMIC2 and chicken IL-18 (chIL-18) was constructed and then delivered to the host by invasive L.P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Immunization with recombinant L . plantarum in chicken also improved humoral and cellular immunity and enhanced resistance to Eimeria tenella [ 54 ]. The results showed that recombinant vaccines constructed by LAB had a good immune protection.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization with recombinant L . plantarum in chicken also improved humoral and cellular immunity and enhanced resistance to Eimeria tenella [ 54 ]. The results showed that recombinant vaccines constructed by LAB had a good immune protection.…”
Section: Discussionmentioning
confidence: 99%
“…Another DNA vaccine was administered in PLGA microparticles against foot-and-mouth disease [ 73 ]. IL-18 has been used as an adjuvant in recombinant bacterial vaccines against porcine circovirus type 2 in pigs [ 74 ] and coccidiosis in chickens [ 75 ]. Additionally, IL-18 was evaluated in a universal influenza virus vaccine, with the most promising results compared with the other cytokines assessed in that study [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been used as a carrier for the construction of immune protective vaccines because of its probiotic effect [ 24 ]. Vaccination of chicks with recombinant L. plantarum NC8 has been shown to improve humoral and cellular immunity and enhance the resistance to Eimeria tenella infection [ 55 ]. Hence, in the present study we used L. plantarum NC8 to construct recombinant Tsgal vaccine.…”
Section: Discussionmentioning
confidence: 99%